A Sudden Increase in Plasma Epinephrine Levels Transiently Enhances Platelet Deposition on Severely Damaged Arterial Wall - Badimon, Lina; Martínez-González, José; Royo, Teresita; Lassila, Riitta; Badimon, José Juan (Thrombosis and Haemostasis, 1999)
Epidemiologic evidence has shown that sympathoadrenal activation plays a triggering role in the onset of acute coronary syndromes. However, its mechanism is not yet clearly understood. The aim of this study was to assess the effect of a sudden increase in epinephrine on platelet deposition on severely damaged vessel wall at shear rate conditions modelling stenotic vessels in the porcine model. The selected epinephrine concentrations (0.5 μmol/l-1 mmol/l) alone or in combination with collagen or ADP did not affect platelet aggregation in vitro either in whole blood or in PRP, although porcine platelets express α2-adrenergic receptors as assessed by PCR. In vitro and ex vivo perfusion experiments were performed using the Badimon chamber at high shear rate conditions (1690 s-1). In vitro, epinephrine (130 nmol/l) increased platelet deposition on severely damaged vessel wall (exposing tunica media; ≈1.6-fold, p <0.05) or immobilized collagen (2.2-fold, p <0.01). Ex vivo perfusion experiments were performed from animals that received intravenous epinephrine infusion for one hour at a low (0.3 μg/kg/min; ≈17 nmol/l in plasma, at 20 min of the infusion) and a high dose (1.0 μg/kg/min; ≈106 nmol/l in plasma, at 20 min of the infusion). Only the low dose temporarily increased platelet deposition on severely damaged vessel wall during the first 30 min of infusion [2.4-fold (p <0.05) and 4.2-fold (p <0.01) at 10 and 30 min of the infusion respectively] declining afterwards. Thus, in flow conditions typical of atherosclerotic arteries, a sudden physiological release of epinephrine can temporarily enhance platelet deposition on severely damaged vessel wall while an extensive exposure leads to refractoriness.
Keywords: Platelets; pig; vessel wall; epinephrine; vascular damage